(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
Inclusive education has become one of the most important directions of contemporary educational development, reflecting the principles of equality, social justice, and human rights. This article examines the social foundations of the inclusive education system from socio-philosophical and pedagogical perspectives. The study analyzes the role of inclusive education in ensuring equal educational opportunities, promoting social integration, and strengthening social cohesion. Particular attention is devoted to the relationship between inclusive education, social justice, human dignity, and sustainable social development. Through theoretical and comparative analysis, the article identifies the social mechanisms that contribute to the effectiveness of inclusive educational environments. The findings indicate that inclusive education serves not only as an educational model but also as a social institution that promotes equal participation, social inclusion, and human development. The article concludes that strengthening the social foundations of inclusive education is essential for building equitable and inclusive societies